A multi‐residue method for 17 anticoccidial drugs and ractopamine in animal tissues by liquid chromatography‐tandem mass spectrometry and time‐of‐flight mass spectrometry. Issue 5 (May 2016) - Matus, Johanna L.; Boison, Joe O.
Abstract : A new and sensitive multi‐residue liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) and liquid chromatography‐quadrupole time‐of‐flight‐mass spectrometry (LC‐QToF‐MS) method was developed and validated for the determination and confirmation of residues of 17 anticoccidials, plus free ractopamine in poultry muscle and liver, and bovine muscle, liver, and kidney tissues. The 17 anticoccidials are lasalocid, halofuginone, narasin, monensin, semduramicin, ethopabate, robenidine, buquinolate, toltrazuril as its sulfone metabolite, maduramicin, salinomycin, diclazuril, amprolium, decoquinate, dinitolmide, clopidol, and the nicarbazin metabolite DNC (N, N1‐bis(4‐nitrophenyl)urea). The analytes were extracted and cleaned up within a 3‐hour period by simply extracting the analytes into a solvent mixture with salts followed by centrifugation, dilution, and filtration. The validated method was used in a pilot study for the analysis of 173 samples that included quail liver, bovine kidney, liver, muscle, and horse muscle. The predominant residues found in this study were monensin, ractopamine, and lasalocid. The results of this pilot study showed that this new method is applicable to real samples, and is fit for use in a regulatory testing programme. © 2016 Her Majesty the Queen in Right of Canada. Drug Testing and Analysis. © 2016 John Wiley & Sons, Ltd. Abstract : The prophylactic use of drugs in animal herds raised in confined areas requires validated methods to monitor for residual drugs in the resulting meat and animal products to avoid human consumption. This validated method has been shown to be fit‐for‐purpose through a pilot study and analysis of regulatory samples for determination of anticoccidials in animal tissues.